Advances in evolutionary developmental biology - Streelman, J. Todd (Jeffrey Todd) (Wiley-Blackwell, 2014)
Providing outstanding breadth of coverage in evo-devo, Advances in Evolutionary Developmental Biology provides a comprehensive review of the milestones of research in evolution and development and outlines the exciting research agenda for the field going forward. Compiling the viewpoints of a diverse group of field experts, this timely text expands the now-mature science of evo-devo into more complex areas of research. This essential reference is destined to become the go-to source for ideas and hypotheses for a new generation of graduate students in evolutionary and developmental biolo.